Être touareg dans le Sud libyen en transition: une citoyenneté encore inachevée - Pauline Poupart (L’Année du Maghreb)
This article draws a portrait of a civil movement named La Lil Tamyiz (“No to discrimination”), formed at the beginning of 2020 by a group of young Tuaregs originating from the regions of Ghat, Ubari and Sebha. It questions, from a socio-historical perspective, the evolution of the mobilisation to access Libyan citizenship undertaken by the Tuareg community since the 1950s. This movement includes an important number of young Tuaregs of Sahelian origins, who were born and raised in Libya but did not benefit from the same rights granted to Libyan citizens. As an illustration, their voting capacity is limited as to their possibility of registering in the public universities of their choice. They also cannot apply for a national passport. The movement's first goal is to gain access to “full” Libyan nationality, meaning naturalisation, inscription on the general population register and obtention of the ‘family booklet’. These inequities are a hurdle in their daily individual and professional lives. They also have negative repercussions by creating a differentiation between “Libyan” Tuaregs and “Sahelian” ones. The first group mentioned is originally part of the Kel Ajjer community that established itself between Algeria and Libya. Despite their historic transnational movements and connections between both countries, they were registered as Libyan citizens when Libya became independent. Since the 1950s, they possess a family booklet that grants them access to political representation and all public services. The “Sahelian” Tuaregs came later to the country, looking for better conditions in the 1970s, as they were hit by repeated droughts and growing political surveillance and repression by the Malian and Nigerien authorities at the time. In addition, in order to improve their living conditions and potential job opportunities, they also found under Ghadafi’s regime the possibility to be trained militarily, hoping to use these skills in further rebellions in their home countries during the 1990s. Some of them did return to Libya after and joined the ones who decided to settle with their families. Despite the decades spent in the Libyan South and the renewed demands for naturalisation, the only papers they possess are identity cards and changing administrative numbers. This lasting distinction in the community currently results in a flawed political representation and questions the ability to be recognised more broadly as a whole and legitimate part of the national ensemble. The first part of the argument will present these militants both as heirs of the instrumental relations that connected the Gadhafi regime with the Tuaregs from Niger and Mali and as representatives of a “new generation” who uses social networks, demonstrations and public addresses to national authorities, hoping to advance the ever-changing administrative procedures engaged during Gadhafi’s time and after. The second part will analyse the limits to peaceful mobilisations like La Lil Tamyiz. If the movement could structure itself and expand in the country and abroad, it is currently constrained in its capacity for action. The main hardships it faces are the blocked political situation at the national level, internal rivalries among the Tuareg community and, most of all, the multiplication of armed groups who confiscated the public space while framing the use of force as the ultimate tool to access rights. This research is based on a review of the leading publications about Tuaregs in Libya, on documents and publications issued by the movement as to a selection of interviews with militants in the country and abroad via written or oral exchanges using social media (Whatsapp, Skype). Additional interviews from my PhD fieldwork in South Algeria and North Niger are also used as complementary elements regarding the experiences of former Malian and Nigerien Tuareg fighters in the “Islamic legion” who have maintained family ties in Libya.